1995
DOI: 10.1093/bja/75.5.531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystalloid and colloid preloading on uteroplacental and maternal haemodynamic state during spinal anaesthesia for caesarean section

Abstract: We have studied the effects of crystalloid 1 litre (lactated Ringer's) or colloid 0.5 litre (hydroxyethyl starch) preloading in 26 healthy parturients undergoing elective Caesarean section under spinal anaesthesia. Maternal placental uterine artery circulation was measured using a pulsed colour Doppler technique with simultaneous measurement of maternal haemodynamics. A high incidence of maternal hypotension was observed during spinal anaesthesia in the crystalloid group (62%) but the incidence was lower in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 11 publications
7
44
2
2
Order By: Relevance
“…The relative hypovolaemia caused by the combination of aortocaval compression and subarachnoid block may lead to placental insufficiency. The incidence of hypotension seems to be unexpectedly high despite preloading with crystalloids (47.4-83%) [1,2] or colloids (17-38%) [3,4] and the use of prophylactic vasoconstrictors (35-80%) [5].The universal practice of employing a 15°left lateral tilt using an obstetric wedge under the right hip [6] or tilting the table leftwards [7] might help to decrease the degree of aortocaval compression but does not guarantee its absence [8]. Maximum displacement of the uterus is best achieved by mechanical displacers.…”
mentioning
confidence: 99%
“…The relative hypovolaemia caused by the combination of aortocaval compression and subarachnoid block may lead to placental insufficiency. The incidence of hypotension seems to be unexpectedly high despite preloading with crystalloids (47.4-83%) [1,2] or colloids (17-38%) [3,4] and the use of prophylactic vasoconstrictors (35-80%) [5].The universal practice of employing a 15°left lateral tilt using an obstetric wedge under the right hip [6] or tilting the table leftwards [7] might help to decrease the degree of aortocaval compression but does not guarantee its absence [8]. Maximum displacement of the uterus is best achieved by mechanical displacers.…”
mentioning
confidence: 99%
“…Inappropriate use of these methods, because of the nature or site of the injuries, may lead to a failure of DVT prophylaxis. An effective alternative to anticoagulation may be vena caval interruption [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Other colloids have been studied in the context of obstetric spinal anaesthesia. Hydroxyethyl starch (HES) 6% has been shown to be more effective at maintaining maternal blood pressure than Ringer's lactate but neither solution can prevent it [14]. A preload of HES 6% combined with Ringer's lactate solution has been shown to be superior to both a gelatin/Ringer's lactate combination and HES alone [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…J. Karinen et al (1995) found that incidence of maternal hypotension in the crystalloid group was 62% as compared to 38% in the colloid group. Colloid preloading has been suggested earlier (Twigly-1985) 66 and tried effectively by many others too.…”
Section: Introductionmentioning
confidence: 96%